PERBANDINGAN METODE PEMBELAJARAN UNPLUGGED PADA MATERI SISTEM KONVERSI BILANGAN PADA MATA PELAJARAN INFORMATIKA KELAS VIII DI SMP NEGERI 6 SAMARINDA - Aldi Febrian, Muhamad; Yudha Saputra, Galih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to compare unplugged learning methods and conventional learning methods in terms of students’ computational thinking skills in Informatics learning. The research employed a quasi-experimental approach using a non-equivalent control group design. The population consisted of eighth-grade students of SMP Negeri 6 Samarinda, with two classes selected as research samples. The experimental class was taught using unplugged learning activities, while the control class received conventional instruction. Data were collected through pretest and posttest instruments to measure students’ computational thinking skills before and after the learning process. Data analysis was conducted using N-Gain to examine the improvement in students’ learning outcomes. The results indicate differences in the improvement of computational thinking skills between the experimental class and the control class, with the experimental class showing higher learning gains.